2020
DOI: 10.4070/kcj.2019.0379
|View full text |Cite
|
Sign up to set email alerts
|

A Close Relationship between Non-Alcoholic Fatty Liver Disease Marker and New-Onset Hypertension in Healthy Korean Adults

Abstract: Background and Objectives Nonalcoholic fatty liver disease (NAFLD) is an excessive accumulation of fat into the liver as a result of increased inflammation and insulin resistance. Although there can be common pathogenic mechanisms for NAFLD and hypertension associated with the development of cardiovascular diseases, little data are showing the association between NAFLD and hypertension in a large-scale cohort study. Thus, we evaluated the ability of the fatty liver index (FLI), a surrogate marker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…However, it is still unclear if management of hypertension would reduce HCC risk. Some prospective cohort studies including subjects with different clinical conditions showed that NAFLD was an independent risk factor for hypertension [45][46][47][48][49][50][51]. A prospective cohort study including 11,350 subjects without prehypertension in 5 years follow-up showed that NAFLD was an independent risk factor of prehypertension, because the severity of NAFLD was positively associated with the risk of prehypertension [52].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still unclear if management of hypertension would reduce HCC risk. Some prospective cohort studies including subjects with different clinical conditions showed that NAFLD was an independent risk factor for hypertension [45][46][47][48][49][50][51]. A prospective cohort study including 11,350 subjects without prehypertension in 5 years follow-up showed that NAFLD was an independent risk factor of prehypertension, because the severity of NAFLD was positively associated with the risk of prehypertension [52].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there have been only 3 studies on the association between FLI level and development of hypertension. 21 , 22 , 23 Logistic regression analyses using 1521 subjects (men/women: 484/1037) in an average follow‐up period of 2.6 years in Korea 21 and 2565 subjects (men/women: 1138/1427) in a follow‐up period of 9 years in France 22 showed that odds ratios for the development of hypertension were higher in the high FLI group than in the low FLI group, although the cumulative incidence of hypertension was not analyzed in those studies. A longitudinal study using 334 280 Korean subjects (men/women: 161 338/172 942) also showed that there was an association between FLI level and the risk of cumulative incidence of hypertension during a median follow‐up period of 5.2 years.…”
mentioning
confidence: 99%
“…A longitudinal study using 334 280 Korean subjects (men/women: 161 338/172 942) also showed that there was an association between FLI level and the risk of cumulative incidence of hypertension during a median follow‐up period of 5.2 years. 23 However, despite the fact that there is a sex difference in the level of FLI, 16 there has been no study in which the relationship between FLI level and development of hypertension was investigated separately in men and women. 21 , 22 , 23 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue, the probable association between NAFLD/NASH and hypertension was presented in general population using national health check-up data. 9) Fatty liver index (FLI) was used as a surrogate marker of NAFLD/NASH, in which FLI was calculated with the formula including triglyceride, gamma-glutamyl transferase (GGT), waist circumference and body mass index. The authors concluded that higher FLI was associated with the increased risk of newly developed hypertension after 2 years.…”
mentioning
confidence: 99%